2019
DOI: 10.1111/jvh.13115
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world effectiveness of sofosbuvir/velpatasvir/voxilaprevir in 573 direct‐acting antiviral experienced hepatitis C patients

Abstract: Sofosbuvir/velpatasvir/voxilaprevir (SOF/VEL/VOX) provides a needed hepatitis C virus (HCV) antiviral option for direct‐acting antiviral (DAA)‐experienced patients. We evaluated the effectiveness of SOF/VEL/VOX for 12 weeks in DAA‐experienced patients with genotype 1‐4 treated in clinical practice. In this observational cohort analysis from the Veterans Affairs’ Clinical Case Registry, 573 DAA‐experienced patients initiating SOF/VEL/VOX were included: 490 genotype 1, 20 genotype 2, 51 genotype 3 and 12 genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 25 publications
3
52
7
Order By: Relevance
“…The safety data of sofosbuvir, velpatasvir and voxilaprevir was based on data from phase II and III clinical trials and real-world studies. [35][36][37][38][39] Headache, diarrhoea and nausea were the most commonly reported adverse events. The incidence of gastrointestinal side effects was greater than with the combination of sofosbuvir and velpatasvir alone.…”
Section: Evidence Quality Notes Gradingmentioning
confidence: 99%
“…The safety data of sofosbuvir, velpatasvir and voxilaprevir was based on data from phase II and III clinical trials and real-world studies. [35][36][37][38][39] Headache, diarrhoea and nausea were the most commonly reported adverse events. The incidence of gastrointestinal side effects was greater than with the combination of sofosbuvir and velpatasvir alone.…”
Section: Evidence Quality Notes Gradingmentioning
confidence: 99%
“…( 41 ) The triple combination of sofosbuvir/velpatasvir/voxilaprevir is highly effective for retreating patients who fail DAA therapy, with cure rates >95% in phase 3 studies, ( 42 ) but real‐world studies suggest reduced cure rates in people with genotype 3 infection, cirrhosis, and those who had failed sofosbuvir/velpatasvir. ( 43,44 ) In the phase 3 trials, there was no apparent impact of RASs, but only a minority of patients had multiclass resistance and 1 patient with virologic breakthrough on treatment had multiple RASs in NS5A (Q30T, L31M, Y93H) and NS3 (Q80K). ( 42 ) Thus, further real‐world studies are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…The RAS profile at retreatment baseline had no influence on the virological response and the patient who relapsed had no detectable RASs at baseline or at virological failure. 36 Other studies presented at the 2018 Annual Meeting of the AASLD confirmed that the combination of sofosbuvir, velpatasvir, and voxilaprevir is safe and effective in DAAexposed patients [61][62][63][64][65] and yields high SVR rates in various groups, including patients with human immunodeficiency virus (HIV) coinfection, 61 patients with compensated cirrhosis, 66 patients who received multiple courses of DAA treatment and selected RASs conferring high-level resistance to NS5A inhibitors, 65,67 or patients who failed to achieve SVR on Table 2 Resistance-associated substitutions (RASs) conferring reduced susceptibility to the corresponding drug classes in in vitro assays and/or selected in patients who failed to achieve SVR on IFN-free, DAA-based regimens (excluding first-generation protease inhibitors telaprevir and boceprevir) Source: Updated from EASL Recommendations on Treatment of Hepatitis C 2018. 2 Note: These RASs and other substitutions at the same positions may be present at retreatment baseline in patients who failed to achieve SVR, suggesting reduced susceptibility to drug(s) from the corresponding class(es).…”
Section: Sofosbuvir/velpatasvir/voxilaprevirmentioning
confidence: 99%
“…glecaprevir/pibrentasvir. 68 Slightly lower SVR rates, of the order of 85%, have been reported in veterans from a realworld cohort previously treated with sofosbuvir/velpatasvir, but the number of patients was small, 65 emphasizing the need for future studies assessing whether retreatment with sofosbuvir/velpatasvir/voxilaprevir yields similar SVR rates regardless of previously administered DAAs.…”
Section: Sofosbuvir/velpatasvir/voxilaprevirmentioning
confidence: 99%